Analysis on Action of Rakthasthambhaka Dravya’s in Asrigdhara with special reference to Abnormal Uterine Bleeding - Noor Fathima; Mamatha K.V (AYUSHDHARA, 2022)
Rakta is the main constituent in the human body as it is considered as vital. Sthambhana means to prevent mobility or block, is one among the Shadvidopakrama and can be well-thought-out as a part of Chaturvidha Chikitsa. Raktasthambhana means to stop excess flow of Rakta because Atyaadhika Raktasrava (excessive menstrual bleeding) may be life threatening so haemostatic measures should be adopted. Asrigdhara defined as excessive and prolonged bleeding during menstruation with or without intermenstrual bleeding. The Nidana’s leading to vitiation of Tridosha’s in Garbhashaya Gata Siras and Artavavaha srotas leading to Artava Atipravrutti. Abnormal uterine bleeding is a common gynaecological complaint with various aetiologies and varied pathophysiological origins. Excessive bleeding during menstruation can restrict with her daily activities, disturb her wellbeing and reducing their efficiency in society. Excessive flow of blood during menstrual and intermenstrual period creates a condition of anaemia in the patient. The Raktasthambhaka Dravya’s are not only helpful for stopping excessive and prolonged bleeding during menstruation but also regularizes menstrual cycle and acts on improving the quality of Rakta Dhatu were discussed in detail in the present paper with their clinical researches.